Utilization of Bananas into Processed Products in the Kusuma Dewi Group, Asahduren Village, Jembrana Regency - A A Made Semariyani; Ni Made Yudiastari; Luh Suariani; Ni Made Ayu Suardani Singapurwa; I Putu Candra; Ni Wayan Yulia Andriani; Ayu Ningtias Mas Puspitayanti; K. Agus Yogi Indrawan; I Wayan Richo Yasa; I Gede Ari Supastiawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
A Banana is a fruit that can bear fruit regardless of the season. Bananas can grow in upland and lowland areas. Bananas are mostly produced in Asahduren Village, a village located in Pekutatan District, which is 75 km from the provincial capital of Bali. This very abundant banana fruit causes the community to be overwhelmed, so many are wasted after being used for traditional ceremonies. Therefore, community service is carried out with counseling methods, training, and product manufacturing practices. The community was given knowledge about processing bananas into banana chips snacks, processed banana jam, banana flour, banana sale, banana brownies and banana cakes, packaging, storage, marketing, entrepreneurship, and business management. With the skill of processing bananas into processed products, the group's income can increase.